Probing the Ternary Complexes of Indoleamine and Tryptophan 2,3-Dioxygenases by Cryoreduction EPR and ENDOR Spectroscopy - Davydov, Roman M. (American Chemical Society, 2010)
[Image: see text] We have applied cryoreduction/EPR/ENDOR techniques to characterize the active-site structure of the ferrous-oxy complexes of human (hIDO) and Shewanella oneidensis (sIDO) indoleamine 2,3-dioxygenases, Xanthomonas campestris (XcTDO) tryptophan 2,3-dioxygenase, and the H55S variant of XcTDO in the absence and in the presence of the substrate l-Trp and a substrate analogue, l-Me-Trp. The results reveal the presence of multiple conformations of the binary ferrous-oxy species of the IDOs. In more populated conformers, most likely a water molecule is within hydrogen-bonding distance of the bound ligand, which favors protonation of a cryogenerated ferric peroxy species at 77 K. In contrast to the binary complexes, cryoreduction of all of the studied ternary [enzyme-O(2)-Trp] dioxygenase complexes generates a ferric peroxy heme species with very similar EPR and (1)H ENDOR spectra in which protonation of the basic peroxy ligand does not occur at 77 K. Parallel studies with l-Me-Trp, in which the proton of the indole nitrogen is replaced with a methyl group, eliminate the possibility that the indole NH group of the substrate acts as a hydrogen bond donor to the bound O(2), and we suggest instead that the ammonium group of the substrate hydrogen-bonds to the dioxygen ligand. The present data show that substrate binding, primarily through this H-bond, causes the bound dioxygen to adopt a new conformation, which presumably is oriented for insertion of O(2) into the C(2)−C(3) double bond of the substrate. This substrate interaction further helps control the reactivity of the heme-bound dioxygen by “shielding” it from water.